IDENTIFICATION OF RISKS IN IMPLEMENTING WATER STRATEGY FOR URBAN COMMUNITIES - KIREITSEVA, HANNA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article develops a comprehensive methodology for identifying and minimizing risks in the implementation of water strategies for urban communities. This research is particularly relevant in the context of Ukraine’s European integration processes and the need to align national water resource management systems with the requirements of the EU Water Framework Directive. Based on the analysis of the water resources of the Zhytomyr urban territorial community, the study identified systematic problems including water quality deterioration, insufficient water protection zones, and exceedance of maximum allowable concentrations of pollutants. The developed methodology is based on the principles of integration, multi-criteria approach, adaptability, and stakeholder orientation. It aligns with international and national standards, including ISO 31000:2018 and relevant legislation. The research proposes a classification of water strategy implementation risks into two main categories: special risks (related to specific strategic goals) and general risks (affecting the implementation of the strategy as a whole), providing a structured approach to risk assessment and mitigation planning. The quantitative risk assessment toolkit includes an integrated risk indicator and three-level scales for assessing probability, impact, and reliability. The proposed formula for calculating the integrated risk indicator (IRI=P×I×R) allows for a comprehensive quantitative risk assessment considering the reliability of available data. The methodology was tested in assessing the pollution risks of the Teteriv River, identifying priority risks (increasing manganese concentration and pollution from untreated discharges) and proposing measures for their minimization, including online monitoring systems implementation, treatment facilities modernization, additional research, and sewage network reconstruction. The practical significance of the results lies in enabling urban communities to systematize water strategy risk management, perform quantitative risk assessment, and reasonably determine priority measures to minimize the most critical risks. This approach contributes to more efficient use of limited community resources, ensuring sustainable water use and supporting European integration processes at the local level.